2015
DOI: 10.1016/j.bandl.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the regions involved in phonological assembly using a novel paradigm

Abstract: HighlightsSequential delivery of letters in words encourages the use of phonological assembly.Greater activation in left SMG, POp and precentral gyrus during sequential delivery.Activation for ‘phonological assembly’ not confounded with stimulus properties.Activation for ‘phonological assembly’ not wholly attributable to processing load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…It was promising to observe that the correlation between L-PMd activity and % accuracy not only increased (standard: r = 0.59; sensitized: r = 0.7) but was also marginally significant (p = 0.02) only after sensitization. Because this task involves overt word generation, the role of left dorsal pre-motor cortex (L-PMd) is relevant as there is evidence that L-PMd along with left pars opercularis (L-POp) is involved in sound sequencing and assembly (Twomey et al, 2015). We also observed a strong (r = 0.55) but less marginally significant (p = 0.08) correlation between sensitized posterior DMN activity and % accuracy.…”
Section: Sensitization Of Task-bold Activitymentioning
confidence: 65%
See 1 more Smart Citation
“…It was promising to observe that the correlation between L-PMd activity and % accuracy not only increased (standard: r = 0.59; sensitized: r = 0.7) but was also marginally significant (p = 0.02) only after sensitization. Because this task involves overt word generation, the role of left dorsal pre-motor cortex (L-PMd) is relevant as there is evidence that L-PMd along with left pars opercularis (L-POp) is involved in sound sequencing and assembly (Twomey et al, 2015). We also observed a strong (r = 0.55) but less marginally significant (p = 0.08) correlation between sensitized posterior DMN activity and % accuracy.…”
Section: Sensitization Of Task-bold Activitymentioning
confidence: 65%
“…From Table 2, we note that L-PMd/L-POp activity is significant (p < 0.01, FWE corrected, < 5% FPR) and detectable only after sensitization. As explained above, L-PMd and L-POp are speech and language eloquent areas that are involved in sound sequencing and phonological processing (Twomey et al, 2015) respectively. Similarly, involvement of anterior posterior cingulate cortex (PCC) was detectable only after sensitization.…”
Section: Sensitization Of Task-bold Activitymentioning
confidence: 99%
“…This is consistent with the finding of more activation in the left frontal opercular sites when subjects read pronounceable nonwords as compared with words (e.g., high frequency consistent and inconsistent words, Fiez et al, 2006 ). It has been suggested that increased opercular activation might be associated with higher processing load when reading nonwords and irregular words, because whole-word processing is not possible and instead phonological assembly processes are used ( Twomey et al, 2015 ). Hence, the association of increased connectivity with the left frontal opercular regions in poor readers may indicate more involvement of phonological processing effort for AVi nonword information.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroanatomical proximity of L-PTr and L-POp allows for a semantic-phonological processing gradient to exist between the two brain regions in order to facilitate the functional integration of information from both the dorsal (phonological processing) and ventral (semantic processing) streams. It should be noted that irrespective of real or pseudo-words, oral articulation involves phonological coding, such that L-POp is likely involved in phonological processing of both real and pseudo-words 37 .…”
Section: Neurocognitive Model Of Oral Readingmentioning
confidence: 99%
“…Following semantic-phonological processing of real words, and phonological processing of pseudo-words, the next step is to assemble sound sequences for the enunciation of real and pseudo-words. It has been shown that left ventral pre-motor cortex is involved in phoneme/sound assembly 37 . Subsequently, the assembled phoneme sequence is compared to the existing phonological output lexicon (dictionary of learned sound sequences), followed by the initiation of the phoneme sequence by the left putamen (L-Put) 38 .…”
Section: Neurocognitive Model Of Oral Readingmentioning
confidence: 99%